ISLAM CONCEPT ABOUT TOLERANCE AND RELIGIOUS FREEDOM - Caco, Rahmawati (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2014)
The discourse of tolerance and religious freedom become the impossibility which cannot be escaped in our plural society life. The main problem is how the concept al-Qurâan in explaining well the case of tolerance and religious freedom. Religious freedom naturally is the foundation for creating religion harmony between religious followers. Without religious freedom, it is impossible to create religion harmony. Religious freedom is the right of every people. The right to convey God is given, and nobody can take it out. Tolerance, freedom, and religion plurality implicitly and explicitly contain in al-Qurâan. The confirmation of al-Qurâan about social group plurality and life necessity amomg groups are developed without limitationas long as have benefits. The acknowledgement of al-Qurâan about social group plurality and the human necessity life is guided without limitation as long as it has profit and benefit. In the case of aqidah and belief, al-Qurâan contains very absolute boarded and there is no bargain, because belief and faith is the case relation between human and their Creature. —– Wacana toleransi dan kebebasan beragama merupakan suatu keniscayaan yang tidak dapat dielakkan dalam kehidupan masyarakat plural.Persoalan utamanya adalah bagaimana konsep al-Qurâan dalam menjelaskan secara lebih baik ihwal toleransi dan kebebasan beragama.Kebebasan beragama pada hakekatnya adalah dasar bagi terciptanya kerukunan antar umat beragama.Tanpa kebebasan beragama tidak mungkin ada kerukunan antar umat beragama.Kebebasan beragama adalah hak setiap manusia. Hak untuk menyembah Tuhan diberikan oleh Tuhan, dan tidak ada seorangpun yang bisa mencabutnya.Toleransi, kebebasan, dan pluralitas beragama secara implisit maupun eksplisit terdapat dalam al-Qurâan. Pengakuan al-Qurâan tentang pluralitas kelompok sosial dan pemenuhan hidup antar kelompok manusia dibina tanpa ada batasnya selama mendatangkan kemaslahatan.Dalam hal aqidah dan keyakinan al-Qurâan memuat garis demarkasi yang sangatÂ pasti dan tidak ada sikap tawar menawar Â karena keyakinan dan keimanan adalah masalah hubungan manusia dan Tuhannya.